Dry needling for manual therapists : points, techniques and treatments, including electroacupuncture and advanced tendon techniques /: points, techniques and treatments, including electroacupuncture and advanced tendon techniques. (2016) - Gyer, Giles; Michael, Jimmy; Tolson, Ben
No abstract available